Capacities of the peruvian army to face new threats to national security - Arrieta Pinedo, Felipe (2020)
The research aimed to determine the extent to which the capacities of the Peruvian Army influenced the way in which new threats to national security were addressed. This research was of a descriptive correlational type, quantitative approach, and the design was non-experimental and cross-sectional. The population consisted of 9,320,140 people, including general officers, superiors and subordinates, technicians and non-commissioned officers of the 1st Multipurpose Brigade, Amazon Protection Brigade, and the population of the cities of Lima and Madre de Dios. The sample was determined through a simple random formula, which included a total of 384 people. The data collection techniques were direct observation and survey, and the instrument used was the Likert style questionnaire, which was composed of 18 items, according to the following analysis variables: capacities of the Peruvian Army and new threats to national security. By correlating the analysis variables, a value of 0.967 was obtained and, according to Rho Spearman's correlation, it was determined that there is a high degree of correlation. In addition, when carrying out the study of crossed tables between the equipment and the new threats against the national security, a value of 0.971 was obtained, for which, the null hypothesis was rejected and the work hypothesis was accepted. Consequently, it was concluded that the capacities of the Peruvian Army significantly influence the new threats to national security.